2020
DOI: 10.18502/ijhoscr.v14i3.3724
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Thrombotic Thrombocytopenic Purpura without Hematological Features

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disease, usually diagnosed with high index of suspicion. The pathophysiology of TTP is due to severe deficiency of von Willebrand factor cleaving protease, known as ADAMTS 13. Early diagnosis is crucial as without treatment TTP is associated with high mortality rate. Plasma exchange is currently the mainstay of treatment. Nonetheless, the classical pentad of microangiopathic hemolytic anemia (MAHA), thrombocytopenia, neurological dysfunction, kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Subsequently a diagnosis of TTP was presumed when a patient presented with the dyad of MAHA and thrombocytopenia, based on the need to promptly treat such patients [ 11 ]. With the discovery that thrombosis of TTP is due to profound ADAMTS13 deficiency [ 11 ], it is increasingly recognized that a lack of MAHA and/or thrombocytopenia does not exclude the diagnosis of TTP, as has been described in various reports in the literature [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In 2002, O’Brien et al [ 3 ] reported two patients who presented with neurological deficits with roughly normal hematological findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently a diagnosis of TTP was presumed when a patient presented with the dyad of MAHA and thrombocytopenia, based on the need to promptly treat such patients [ 11 ]. With the discovery that thrombosis of TTP is due to profound ADAMTS13 deficiency [ 11 ], it is increasingly recognized that a lack of MAHA and/or thrombocytopenia does not exclude the diagnosis of TTP, as has been described in various reports in the literature [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In 2002, O’Brien et al [ 3 ] reported two patients who presented with neurological deficits with roughly normal hematological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Four more cases of TTP presenting with symptoms suggestive of macrovascular arterial involvement and minimal schistocytes were reported in 2012 [ 6 ]. In more recent years, several cases were reported [ 7 , 8 , 9 ] in which TTP either first presented or relapsed as CVA without clear signs of MAHA and/or thrombocytopenia. Notably, it has been almost seventeen years since publication of the earliest reports of such atypical presentations of TTP [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not considered a typical manifestation of the disease, it is seen in many cases [4]. Such atypical manifestations necessitate heightened clinical vigilance to ensure prompt and accurate diagnosis, which is critical for initiating lifesaving interventions [5]. The mainstay of treatment for TTP is plasma exchange, which has significantly improved the prognosis of the disease by removing circulating autoantibodies and replenishing deficient ADAMTS13 [6].…”
Section: Introductionmentioning
confidence: 99%